The Relationship Between Dialysis Patients' Quality of Life and Caregivers' Quality of Life - Nagasawa, Hiroyuki; Sugita, Ikuto; Tachi, Tomoya; Esaki, Hiroki; Yoshida, Aki; Kanematsu, Yuta; Noguchi, Yoshihiro; Kobayashi, Yukio; Ichikawa, Etsuko; Tsuchiya, Teruo; Teramachi, Hitomi (Frontiers in Pharmacology, 2018)
Patients on dialysis require caregiving and assistance in their daily lives from family members and/or others for hospital visitation and supervised administration. This places a considerable burden on caregivers, which can in turn influence caregivers' quality of life (QOL). We recruited dialysis patients and their caregivers to elucidate how the QOL of patients relates to that of their caregivers'. Patients completed the EuroQol 5-Dimension scale (EQ-5D) and Kidney Disease Quality of Life-Short Form. Caregivers completed the EQ-5D and Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). We calculated utility index values for the EQ-5D, and physical, mental (MCS), and role-social component summary scores for the SF-36. Compared to national norms, the caregivers of dialysis patients tended to have poor physical health-related QOL but normal mental health-related QOL, as also found with patients. The multivariate analysis revealed that ≥ median dialysis period and ≥ average burden of kidney disease were significantly related to caregiver MCS score (odds ratios; 6.79 and 9.89, respectively). Caregivers tended to have lower physical health-related QOL if their patients had high social QOL, and lower mental health-related QOL during the early stage of the patient's dialysis treatment, and when patients experienced low disease-targeted QOL.